Case Report: Diagnosis of a Choroidal Malignant Melanoma - Hensel, Gordon (Canadian Journal of Optometry, 1981)
Only one province in Canada has the privilege of using diagnostic pharmaceuticals at the time of this writing. (New Brunswick.) Many provincial associations are attempting to pass legislation enabling optometrists the use of such pharmaceuticals but surprisingly, have met opposition from some of its own members. This case report should be read by anyone who exhibits a negative attitude towards the use of diagnostic pharmaceuticals. The author is presently working in association with an ophthalmologist and has the use of such pharmaceuticals under his auspices.